2018
DOI: 10.1007/s00213-018-4958-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of atypicality of bupropion inferred from its receptor engagement in nervous system tissues

Abstract: Despite decades of clinical use and research, the mechanism of action (MOA) of antidepressant medications remains poorly understood. Selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs) are the most commonly prescribed antidepressants—atypical antidepressants such as bupropion have also proven effective, while exhibiting a divergent clinical phenotype. The difference in phenotypic profiles presumably lies in the differences among the MOAs of SSRIs/SNRIs and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(78 reference statements)
0
2
0
1
Order By: Relevance
“…Bupropion is a dopamine/norepinephrine reuptake inhibitor. Although the precise mechanism of action of bupropion is unknown, it is theorized to inhibit norepinephrine and dopamine reuptake and, thus, has been shown to increase neurotransmission of dopamine and norepinephrine in the central nervous system 8 . Amantadine is a dopamine agonist (anti-Parkinson agent), a weak noncompetitive N -methyl- d -aspartate receptor antagonist, and has indirect anticholinergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Bupropion is a dopamine/norepinephrine reuptake inhibitor. Although the precise mechanism of action of bupropion is unknown, it is theorized to inhibit norepinephrine and dopamine reuptake and, thus, has been shown to increase neurotransmission of dopamine and norepinephrine in the central nervous system 8 . Amantadine is a dopamine agonist (anti-Parkinson agent), a weak noncompetitive N -methyl- d -aspartate receptor antagonist, and has indirect anticholinergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies concluded that FLX was effective to normalize BDNF (16, 17), enhance neurogenesis (18, 19), and inhibit GLU transmission (20, 21). Besides these, the effects of FLX on DA, NE, and 5-HT neurotransmission (22, 23) as well as neuroinflammatory factors (7, 8) were widely verified. Therefore, in this study, we also investigated the relationship between 5-HT levels, TNF-α mRNA expression, and the comorbidity of pain and depression and the effect of FLX on these measures.…”
Section: Introductionmentioning
confidence: 99%
“…Inicialmente indicada para tratamento do transtorno depressivo. (ALKONDON;ALBUQUERQUE, 2005;KIM et al, 2018;LERMAN et al, 2006;LERMAN et al, 2003).…”
Section: Introductionunclassified